The Variation of SolarWind Correlation Lengths OverThree Solar Cycles - Wicks,RT; Owens,MJ; Horbury,TS (Solar Physics, 2010)
We present the results of a study of solar wind velocity and magnetic field correlation lengths over the last 35 years. The correlation length of the magnetic field magnitude λ|B| increases on average by a factor of two at solar maxima compared to solar minima. The correlation lengths of the components of the magnetic field λBXYZ and of the velocity λVYZ do not show this change and have similar values, indicating a continual turbulent correlation length of around 1.4 × 106 km. We conclude that a linear relation between λ|B|, VB2, and Kp suggests that the former is related to the total magnetic energy in the solar wind and an estimate of the average size of geoeffective structures, which is, in turn, proportionalto VB2. By looking at the distribution of daily correlation lengths we show that the solarminimum values of λ|B| correspond to the turbulent outer scale. A tail of larger λ|B| values is present at solar maximum causing the increase in mean value.